Il „De magia” e la cultura popolare - Bologna, Orazio Antonio (Collectanea Philologica, 2019)
The brief, but interesting, work by Apuleius constitutes a fixed point both to delineate the biography of the famous African rhetorician, a native of Madaura, and to trace a picture with quite defined outlines on the social and cultural, economic and political aspect, in which he was paying the Roman Empire in the second century aD, especially in that rich southern Mediterranean area. In this short essay the close relationship between culture and magic is highlighted. In culturally backward populations, the educated person is often referred to as a magician, a name which, with its semantic nuances, continues today, especially in some villages of southern Italy. So magician, both in the singular and in the plural, means both the educated person and those who are able to spell or predict the future.